The role of inositol in improving fertility in patients with PCOS - Turek, Kamila; Greguła, Anna; Stachyrak, Karol; Mika, Dawid; Kłos, Aleksandra; Mazur, Bartosz; Lambach, Maciej; Pawlicki, Mateusz; Mazurek, Aleksandra; Wilanowska, Wiktoria (Journal of Education, Health and Sport, 2024)
Introduction and purpose Polycystic ovary syndrome is a common reproductive disorder, accompanied primarily by hyperandrogenism and insulin resistance. Myo-inositol (MI) and D-chiro-inositol (DCI), have emerged as potential therapeutic agents due to their role as insulin sensitizers. This article examines the effects of inositol therapy on fertility in women with PCOS and its role in assisted reproductive technology (ART). Studies suggest that inositols alleviate irregular menstruation, reduce androgen levels and positively affect ovulation rates. MI supplementation has also shown positive effects during controlled ovarian hyperstimulation and IVF procedures, reducing the required FSH dose and cycle length. However, despite positive results on ovulation and menstrual regularity, the article indicates the need for further studies to establish inositol as standard ART therapy in patients with PCOS. Material and methods The following review was based on articles from the PubMed and Google Scholar databases. Key search terms included polycystic ovary syndrome; assisted reproductive treatment, insulin resistance, inositols, Myo-inositol, D-chiro-inositol. Conclusions Inositols are a promising therapeutic option for women with PCOS. They have been shown to have positive effects on improving insulin sensitivity and fertility. However, despite inositol's safety and easy availability, the ideal dose and timing of use, the appropriate MI/DCI ratio, as well as the potential side effects of excess DCI and the problem of inositol resistance, require further comprehensive studies.